(untitled) (Bangladesh Journal of Botany, 2024)
The present article deals with the evaluation of the existing tree species diversity in the Ramna areas of Dhaka city. Both random and stratified random quadrat sampling were used for the data collection from July 2021 to June 2022. The study identified a total of 156 tree species in 46 families. Among the sampling areas, 115 tree species were found in Ramna Park, 61 tree species in Suhrawardy Udyan, and 98 tree species in the Dhaka University area. The sampling areas overlapped significantly with many tree species. Among the species, 33% of the species were of ornamental value, followed by timber (24%), medicinal (21%), fruit (19%), and wildlife-supporting (3%). 51% of the species belonged to exotics and 49% were native. The most abundant species were Swietenia mahagoni in Ramna Park and Dhaka University and Eucalyptus camaldulensis in Suhrawardy Udyan. Based on the important value index, the most dominant species were S mahagoni in Ramna Park and Dhaka University and Ficus elastica in Suhrawardy Udyan. Among the top 15 most abundant and dominant trees, nine belonged to exotics, and the rest were native. The Shannon diversity index value ranged from 3.83 to 4.39. Ramna Park showed the highest index value (4.39), followed by Dhaka University (3.91) and Suhrawardy Udyan (3.83). Stakeholder’s consultations revealed that on average 90% of the support was found for management strategies such as native enrichment, reducing exotic dominance, planting purposeful trees, heritage plantations, and expert consultation during plantation. Identified threats included construction works, exotic presence, lack of native seedlings, and low awareness. Recommendations include promoting the dominance of native species, gradual exotic replacement, enhancing wildlife-supporting species, increasing public awareness, and integrating expert opinions into urban plantation programs. Bangladesh J. Bot. 53(3): 605-617, 2024 (September)